Descriptors of a New Morphotype of One Stripe Spiny Eel, Macrognathus aral(Bloch & Schneider, 1801), Family: Mastacembelidae - KUMARI, S; Sarkar, U K; SWAIN, H S; BHATTACHARYA, S; DAS, B K (The Indian Journal of Animal Sciences, 2022)
The new ocelli variant of Macrognathus aral (Bloch & Schneider, 1801) under Mastacembelidae family was recorded from Gangetic Wetlands of North 24 Parganas, West Bengal, India. The new variant can be considered as a potential ornamental fish apart from high valued food fish, due its more number of ocelli in both dorsal and anal fin base of the body surface, which comparable to other commercially important M. aral.